Legal Analysis of Collusion in Government Goods/Services Procurement Tenders From the Perspective of Good Governance Principles in Support of Sustainable Development (Case Study No 17/Kppu-L/2022): Analisis Hukum tentang Kolusi dalam Tender Pengadaan Barang/Jasa Pemerintah dari Perspektif Prinsip Tata Kelola yang Baik untuk Mendukung Pembangunan Berkelanjutan (Studi Kasus No. 17/Kppu-L/2022) - Niken Dwi Amanda; Andriyanto Adhi Nugroho (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Public procurement plays a strategic role in realizing good governance and sustainable development, yet it remains vulnerable to collusion that undermines transparency, accountability, efficiency, and fair competition. Specific background: In Indonesia, bid rigging in government procurement continues to dominate competition law violations, as reflected in KPPU Decision No. 17/KPPU-L/2022 concerning the Taman Ismail Marzuki revitalization project. Knowledge gap: Previous studies have largely discussed tender collusion normatively, but have not sufficiently integrated good governance principles with concrete enforcement mechanisms in the context of sustainable development. Aims: This study aims to analyze the legal implications of tender collusion from a good governance perspective and to identify effective supervisory mechanisms to prevent its recurrence. Results: Using a normative juridical approach with statute and case analyses, the study finds that the collusion systematically violated transparency through unjustified tender cancellation, accountability through the absence of administrative responsibility, and efficiency and fair competition through directed re-tendering. Novelty: This research explicitly links tender collusion, good governance principles, and sustainable development goals within a single analytical framework. Implications: Strengthening integrated oversight by KPPU, optimizing electronic procurement systems, enhancing public participation, and enforcing competition law consistently are essential to ensuring integrity-based procurement and supporting sustainable national development. Highlights: Tender collusion systematically violates transparency, accountability, and fair competition in government procurement. Weak oversight mechanisms enable bid rigging, resulting in inefficiency and potential losses to public finances. Integrated supervision, digital procurement systems, and strong law enforcement are crucial to support sustainable development. Keywords: Public Procurement, Tender Collusion, Good Governance, Competition Law, Sustainable Development